Molecular Docking, Synthesis and Antibacterial activity of sulphdiazine drug modification and studying their PC3 by MTT - Sadiq S. Sadiq; Raghad Haddad; Hassan Hadi Kadhim; Abbas K. Abbas; Ruqaya K. Abbas (Academia One, 2024)
In this study, we report a novel imine-amoxicillin synthesis (A1-A3) by reacts Sulfadiazine with different aldehydes such as 2-bromobenzaldehyde, 4-propoxybenzaldehyde, and 4- butoxybenzaldehyde. The derivatives (A1-A3) were characterized by spectroscopic technique, such as FT‐IR and 1H-NMR spectroscopy. All the synthesized derivatives were evaluated in vitro against different microorganisms such as Bacillus subtilis, Streptococcus pneumonia, E. coli, and Bacillus subtilis by zone inhibition method. The findings demonstrated that certain derivatives exhibit superior antibacterial properties in comparison to the efficacy of the original drug. The evaluation of derivative 1 as anticancer (breast cancer) by MTT assay and give a positive result after 24 h more than 48 h.
Keywords: Imine; Sulfadiazine; Schiff base